Politik Hukum dalam Penyelenggaraan Kekuasaan Eksekutif di Indonesia - Amos Harita; Ismaidar Ismaidar; Tamaulina Br Sembiring (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Legal politics in the implementation of executive power in Indonesia, which is an integral part of the government system based on the constitution. Legal politics not only determines the direction and content of government policy, but also reflects the power relations between the executive, legislative and judicial institutions. This research aims to analyze how legal politics influences decision making at the executive level, with a focus on the role of the president in the presidential system, regulatory challenges, and political dynamics that influence the implementation of law in Indonesia. A qualitative approach with descriptive-analytical methods was used in this research, through literature review, analysis of legal documents, and evaluation of executive policies. The research results show that legal politics in Indonesia is characterized by challenges such as regulatory disharmony, the dominance of executive power in the presidential system, and political intervention in the legislative process. This situation has the potential to weaken the principles of rule of law and democracy. However, legal politics also functions as a transformation tool to strengthen fair, accountable and transparent governance. Legal political reform through harmonization of regulations, strengthening supervisory mechanisms, and empowering the community in the legislative process is very necessary to create a democratic and just legal system. This paper recommends the need to strengthen checks and balances between state institutions, consistent legal policies that are in line with the constitution, as well as legal education for the public so they can participate actively in the political process.